Supernatants of irritable bowel syndrome mucosal biopsies impair human colonic smooth muscle contractility. Issue 2 (12th September 2016) - Guarino, M. P.; Barbara, G.; Cicenia, A.; Altomare, A.; Barbaro, M. R.; Cocca, S.; Scirocco, A.; Cremon, C.; Emerenziani, S.; Stanghellini, V.; Cicala, M.; Severi, C.
Abstract: Background: Changes in intestinal motility are likely to contribute to irritable bowel syndrome (IBS) pathophysiology. The aim of the study was to investigate the effects of IBS mucosal supernatants on human colonic muscle contractility. Methods: Supernatants were obtained from biopsies of 18 IBS patients—nine with constipation (IBS‐C) and nine with diarrhea‐predominant IBS (IBS‐D)—and nine asymptomatic subjects, used as controls. Colonic circular smooth muscle strips or isolated cells (SMC) were exposed to control or IBS supernatants. Spontaneous phasic contractions on strips and morphofunctional parameters on cells were evaluated in basal conditions and in response to acetylcholine (Ach). Incubation with IBS supernatants was also conducted in the presence of antagonists and inhibitors (namely histamine, protease and prostaglandin antagonists, nuclear factor‐kappa B inhibitor, catalase, NADPH oxidase inhibitor, and the cAMP‐ and/or cGMP‐cyclase inhibitors). Key Results: Exposure to IBS‐C and IBS‐D supernatants induced a significant reduction in basal tone and Ach‐elicited contraction of muscle strips and a significant shortening and impairment of Ach contraction of SMCs. The NADPH oxidase inhibitor prevented the effect of supernatants, while the protease antagonist only IBS‐C effect. No effect was observed with the other antagonists and inhibitors. Dilution of IBS‐D supernatants partially restored the effects only on SMCs, whereas dilution of IBS‐C supernatants significantly reverted the effects on muscle strips and Ach‐elicited response on SMC. Conclusions & Inferences: Supernatants from mucosal biopsies of IBS patients reduce colonic contractility. The observed impairment was concentration dependent, likely occurring through intracellular oxidative stress damage, involving different neuromotor mechanisms depending on the IBS subtype. Abstract : The aim of the study was to investigate the effects of IBS mucosal supernatants on human colonic muscle contractility. Supernatants were obtained from biopsies of IBS patients and asymptomatic subjects. IBS supernatants reduced colonic contractility mucosal likely through muscular intracellular oxidative stress damage. Depending on the IBS subtype, further different neuromotor mechanisms are involved. View the podcast on this paper at the following sites: iTunes:https://itunes.apple.com/gb/podcast/neurogastroenterologymotility/id1187965021 YouTube:https://www.youtube.com/watch?v=lgM5hT7ZcUI